Numerical Assessment of Multi-Cell Thin-Walled Beams under Three-Point Bending for Automotive Safety - Kopar, Mehmet; Sömer, Medeni; Arı, Ali (Fırat University, 2026)
In this study, the impact strength of automotive side door beams reinforced with multi-cell thin-walled structures was investigated under three-point bending loads. Six different configurations (cylindrical and square outer geometries with 3, 4, and 5 inner cells) made of AA6063-T1 aluminum alloy were analyzed using the finite element method. The models developed in HyperMesh were validated with the experimental data of Zhang and Fu, and an error of less than 1.1% was achieved. The results revealed that increasing the number of inner cells significantly increased the energy absorption, average crushing force, and specific energy absorption. The square-profile K5 design achieved the best performance with 0.1617 kJ EA and 0.885 kJ/kg SEA, outperforming its cylindrical counterpart (S5) by 43% and 13%, respectively. The square geometries also exhibited a 69% higher peak crushing force due to their superior vertical load-carrying behavior. The findings indicate that multicellular thin-walled structures offer significant advantages over traditional single-cell designs, providing up to 27-42% improvement in crash performance and are an effective design strategy for lightweight automotive safety components.

Bu çalışmada, çok hücreli ince duvarlı yapılarla güçlendirilmiş otomotiv yan kapı kirişlerinin üç noktalı bükülme yükleri altında çarpma dayanıklılığı araştırılmıştır. AA6063-T1 alüminyum alaşımından yapılmış altı farklı konfigürasyon (3, 4 ve 5 iç hücreli silindirik ve kare dış geometriler) sonlu elemanlar yöntemi kullanılarak analiz edilmiştir. HyperMesh'te geliştirilen modeller, Zhang ve Fu'nun deneysel verileriyle doğrulanmış ve %1,1'den daha az hata elde edilmiştir. Sonuçlar, iç hücrelerin sayısının arttırılmasının enerji emilimini, ortalama kırma kuvvetini ve spesifik enerji emilimini önemli ölçüde arttırdığını ortaya çıkarmıştır. Kare profilli K5 tasarımı, 0,1617 kJ EA ve 0,885 kJ/kg SEA ile en iyi performansı elde ederek silindirik muadilini (S5) sırasıyla % 43 ve %13 oranında daha iyi değerlere sahip olduğu belirlenmiştir. Kare geometriler ayrıca üstün dikey yük taşıma davranışı nedeniyle % 69 daha yüksek tepe kırma kuvveti göstermiştir. Bulgular, çok hücreli güçlendirilmiş kare yapıların, geleneksel tek hücreli tasarımlara göre önemli avantajlar sunduğunu, çarpışma performansında %27-42'ye kadar iyileşme sağladığını ve hafif otomotiv güvenlik bileşenleri için etkili bir tasarım stratejisi olduğu belirlenmiştir.
Otomotiv Güvenliği Açısından Çok Hücreli İnce Duvarlı Kirişlerin Üç Nokta Bükülme Altında Sayısal Değerlendirilmesi
Keywords: Dynamics; Vibration and Vibration Control; Dinamikler; Titreşim ve Titreşim Kontrolü